Characteristics of global port phytoplankton and implications for current ballast water regulations. (June 2020) - Soler-Figueroa, Brenda M.; Fontaine, Diana N.; Carney, Katharine J.; Ruiz, Gregory M.; Tamburri, Mario N.
Abstract: The International Maritime Organization and U.S. Coast Guard have implemented regulations to reduce introductions of non-indigenous species via ballast water (BW). For phytoplankton, regulations limit discharges to <10 live/viable cells mL −1 (size: 10–50 μm), ignoring other size fractions. Additionally, challenge conditions of 100 (shipboard) and 1000 (land-based) cells mL −1 are required in BW management system certification testing. How these requirements correspond to natural phytoplankton populations is poorly resolved. We analyzed phytoplankton samples from 31 major ports to evaluate: a) how natural communities compare to challenge requirements and b) abundances of unregulated size fractions (i.e., <10 and ≥50 μm). None of the ports met land-based challenge conditions, and only 32% met requirements for shipboard testing. Approximately 71% of organisms ≥50 μm were centric diatoms, also unregulated by current protocols. This study demonstrates that current regulations do not consider natural phytoplankton populations, limiting control efforts for potentially harmful non-indigenous species. Graphical abstract: Unlabelled Image Highlights: None of the major ports surveyed met IMO/USCG land-based challenge conditions. Phytoplankton <10 μm comprised over 80% of total abundance and yet are unregulated. Phytoplankton ≥50 μm reached densities of 10 7 cells m −3 and are ignored by protocols.